Can developmental trauma disorder be distinguished from posttraumatic stress disorder? A symptom-level person-centred empirical approach. Issue 2 (19th December 2022) - Ford, Julian D.; Charak, Ruby; Karatzias, Thanos; Shevlin, Mark; Spinazzola, Joseph
ABSTRACT: Background: Developmental Trauma Disorder (DTD) is a proposed childhood psychiatric diagnosis for psychopathological and developmental sequela of victimization and attachment trauma extending beyond posttraumatic stress disorder (PTSD). Objective: To determine whether a sub-group of trauma-impacted children is characterized by symptoms of DTD that extend beyond, or co-occur with, the symptoms of PTSD. Method: Person-centred Latent Class Analyses (LCA) were done with data from 507 children (ages 7–18 years, ( M  = 12.11, SD  = 2/92); 49% female) referred to the study by mental health or paediatric clinicians. Results: A four class solution was optimal (LMR = 398.264, p  < .001; Entropy = .93): (1) combined DTD + PTSD ( n  = 150); (2) predominant DTD ( n  = 156); (3) predominant PTSD ( n  = 54); (4) minimal symptoms ( n  = 147). Consistent with prior research, the DTD + PTSD class was most likely to have experienced traumatic emotional abuse and neglect ( X 2 (3)   = 16.916 and 28.016, respectively, p  < .001), and had the most psychiatric comorbidity ( F (3, 502)   = 3.204, p  < .05). Predominant DTD class members were most likely to meet criteria for Oppositional Defiant Disorder (ODD) ( X 2 (3)  = 84.66, p  < .001). Conclusion: Symptoms of DTD may occur with, or separately from, PTSD symptoms. Children with high DTD|+PTSD symptoms had extensive psychiatric comorbidity, while those with high DTD symptoms and minimal PTSD symptoms were highly likely to meet criteria for ODD. In clinical and research assessment and treatment of children with complex psychiatric comorbidity or disruptive behaviour problems, symptoms of DTD should be considered, both along with, and in the absence of, PTSD symptoms. HIGHLIGHTS: Assessing Developmental Trauma Disorder (DTD) enables clinicians to identify trauma-impacted children who have particularly complex symptoms that exacerbate the psychiatric comorbidity related to PTSD and that extend beyond PTSD to include externalizing problems.